PTH-085 Routine duodenal biopsy for coeliac disease is not cost effective. (23rd September 2015) - Chakrabarty, G; Dambha, H; Lawrence, R; Zar, S; Mahmood, A
Abstract : Introduction: The prevalence of coeliac disease in UK is about 1.5%. Serology provides a relatively cheap and non-invasive means for diagnosis. IgA endomysial (EMA) and IgA anti-tissue transglutaminase (tTG) antibodies are routinely used as a screening tool and carry high sensitivity and specificity. However duodenal biopsy is the accepted gold standard for diagnosis of coeliac disease. Adult coeliac disease generally presents with anaemia and/or non-specific GI symptoms. Both BSG and NICE guidelines recommend that patients with unexplained anaemia should be screened for coeliac disease. If coeliac serology is negative then small bowel biopsies are generally not necessary. Despite this many patients have duodenal biopsy during upper GI endoscopy. Random duodenal biopsies result in increased cost and workload. Aim: To evaluate the diagnostic yield of a routine duodenal biopsy. Methods: Retrospective analysis of all duodenal biopsies undertaken between April-July 2009 was done. Endoscopy records, serology and histology records were reviewed. Results: Total of 103 cases (45M, 58F, mean age 62.6±19.4 years) were examined during the 4-month period. Most common indication was anaemia (57.7%), followed by GI symptoms (17.3%), and weight loss (14.4%). 98 cases were taken for final analysis (5 excluded – 3 biopsies taken to exclude malignancy and 2 for coeliac disease follow-up). Only 1 biopsy out of 98 was diagnostic of coeliac disease, another biopsy showed mild inflammatory changes of uncertain significance and 96 (97.9%) were normal. 18 cases had serology prior to biopsy, out of them 4 had positive tTG, however only one of them was positive for both tTG and EMA and was confirmed coeliac disease on biopsy as well. 80 out of 98 (81.6%) cases had no serology done. All of these had normal histology. Only 10 out of 60 (16.6%) anaemia cases had serology recorded prior to duodenal biopsy. Conclusion: This study demonstrates that coeliac serology as a screening tool is greatly underutilised and duodenal biopsy is being used as the first choice test for diagnosis of coeliac disease. Despite BSG and NICE guidelines, only 16% of patients with anaemia had serology prior to duodenal biopsy. This may be due to the fact that these patients would have needed endoscopy, so it may have been considered convenient to perform duodenal biopsy at the same time. The cost of serology and histology is about £10 and £35, respectively. Therefore appropriate use of diagnostic tools can result in substantial cost saving. We need more stringent implementation of local protocols to facilitate greater adherence to national guidelines. The prevalence of coeliac disease in our population (1.02%) is in keeping with UK population.